The construct of policy leadership: a conceptual framework - Alias, Noryati; Ismail, Azahari (Human Resource Management Academic Research Society, 2017)
This paper provides a framework in defining and presenting the concept of “policy leadership”. Policy leadership are activities that leaders in organizations take to guarantee that the internal and external policy environments keep on being beneficial to the purpose, culture, and changing circumstances of the organization. Policy leadership is not just restricted to the acknowledgment of policy unquestioningly, yet it is likewise worries on the improvements, and changes but it provides the basis for policy execution and implementation in organizations. This type of leadership is significantly important for leaders who are encircled and enclosed with internal and external policies in their organizations that need them to deal proactively and positively within the policies for organizational well-being and its effectiveness. This emerging concept will assists leaders in understanding the ‘what’ and ‘why’ of policy leadership. Besides that, policy leadership provides an opportunity for understanding the role of leaders engaging in policies to achieve organizational effectiveness. However, future research is needed to empirically validate the concept through systematic investigations that sheds light on the constructs and later devise a scale to measure policy leadership.